Construct Validity and Internal Consistency Reliability of Mental Health Monitoring Instrument for Technical University Students - Pua, Poh Keong; Lee, Ming Foong; Lai, & Chee Sern (Journal of Technical Education and Training, 2019)
This study was conducted to generate empirical evidence on the construct validity and internal consistency reliability of the item of a mental health instrument. Construct validity through the Face validity and content validity by expert looking at the items in the questionnaire and agreeing that the item is valid measure of the concept. However these studies more focus on the validation stage (quantitative data) of the research instrument. The reliability was examined by analysis SPSS to determine the internal consistency reliability using Cronbach’s Alpha. A Validation study with a random sample of 50 respondents undergraduate students from University Tun Hussein Onn Malaysia (UTHM). The internal consistency reliability of the construct depression, anxiety, stress and fear was very impressive with Cronbach’s alpha value in the range 0.847 to 0.865. Each item from each constructs, only seven items from overall 40 items with the weak coefficient correlation but each item still in the good internal consistency reliability with the range 0.8 to 0.9. In conclusion, this study has established valid construct for development of instrument for assessing the mental health level to improved mental health well-being and academic performance.